Revision of the water-holding frogs, Cyclorana platycephala (Anura: Hylidae), from arid Australia, including a description of a new species - Anstis, Marion; Price, Luke C.; Roberts, J. Dale; Catalano, Sarah R.; Hines, Harry B.; Doughty, Paul; Donnellan, Stephen C. (Zootaxa, 2016)
The water-holding frog, Cyclorana platycephala, occurs in the Australian arid and semi-arid zones but not in the central Australian deserts. Recent inspection of morphological variation in adults and larvae suggests that the taxon comprises three regional populations: eastern, northern and western that may each represent separate species. To assess the systematic status of these populations, we documented phylogenetic relationships using mitochondrial and nuclear DNA markers, divergence in adult and larval morphology and male advertisement call. Our molecular genetic data demonstrates that the western population of C. platycephala is not the sister taxon of eastern and northern representatives of this nominate species, as the latter two are more closely related to another morphologically distinct species, C. verrucosa. Discriminant Function Analysis of 14 morphological traits in adults and 15 in larvae showed a high degree of morphological differentiation of western versus eastern/northern C. platycephala. Calls of eastern and western populations differed in duration, pulse rate, frequency and especially in amplitude modulation pattern across the call duration. We describe the western population as a new species, whose range is contained entirely within Western Australia. In addition, we redescribe Cyclorana platycephala, quantify morphological and genetic differences between the eastern and northern populations, and conclude that these data support recognition of a single species, Cyclorana platycephala, for populations found in New South Wales, the Barkly Tablelands and south-eastern Northern Territory, Queensland and South Australia.